The effects of crowding and toxicant on biological food - chain system: a mathematical approach - Babu A., Raveendra; Gupta, Srajan; Nisha Rathaur; Agarwal, Tanishka; Sharma, Mamta (KOMUNITAS Analisis Matematika INDONESIA, 2024)
This work considers and studies a prey predator mathematical system to explain the behaviour and impacts of a food-chain system in the presence of toxicant and crowding. According to the system, only prey species defend themselves by releasing toxins. Using stability requirements, all possible equilibrium points of the system are discussed for local stability. It has been noted that when the toxicant effect or the crowding effect are present, the system under consideration will survive. Lastly, numerical simulation is done to validate the analytical findings.